High Cholesterol Diet Exacerbates Blood-Brain Barrier Disruption in LDLr–/– Mice: Impact on Cognitive Function - de Oliveira, Jade (J Alzheimers Dis, 2020)
BACKGROUND: Evidence has revealed an association between familial hypercholesterolemia and cognitive impairment. In this regard, a connection between cognitive deficits and hippocampal blood-brain barrier (BBB) breakdown was found in low-density lipoprotein receptor knockout mice (LDLr–/–), a mouse model of familial hypercholesterolemia. OBJECTIVE: Herein we investigated the impact of a hypercholesterolemic diet on cognition and BBB function in C57BL/6 wild-type and LDLr–/–mice. METHODS: Animals were fed with normal or high cholesterol diets for 30 days. Thus, wild-type and LDLr–/–mice were submitted to memory paradigms. Additionally, BBB integrity was evaluated in the mice’s prefrontal cortices and hippocampi. RESULTS: A tenfold elevation in plasma cholesterol levels of LDLr–/–mice was observed after a hypercholesterolemic diet, while in wild-type mice, the hypercholesterolemic diet exposure increased plasma cholesterol levels only moderately and did not induce cognitive impairment. LDLr–/–mice presented memory impairment regardless of the diet. We observed BBB disruption as an increased permeability to sodium fluorescein in the prefrontal cortices and hippocampi and a decrease on hippocampal claudin-5 and occludin mRNA levels in both wild-type and LDLr–/–mice treated with a hypercholesterolemic diet. The LDLr–/–mice fed with a regular diet already presented BBB dysfunction. The BBB-increased leakage in the hippocampi of LDLr–/–mice was related to high microvessel content and intense astrogliosis, which did not occur in the control mice. CONCLUSION: Therefore, LDLr–/–mice seem to be more susceptible to cognitive impairments and BBB damage induced by exposure to a high cholesterol diet. Finally, BBB disruption appears to be a relevant event in hypercholesterolemia-induced brain alterations.